Arginase-1 specific CD8+ T cells react toward malignant and regulatory myeloid cells - Hannah Jorinde Glöckner; Evelina Martinenaite; Thomas Landkildehus Lisle; Jacob Grauslund; Shamaila Ahmad; Özcan Met; Per Thor Straten; Mads Hald Andersen (OncoImmunology)
Arginase-1 (Arg1) is expressed by regulatory myeloid cells in the tumor microenvironment (TME), where they play a pro-tumorigenic and T-cell suppressive role. Arg1-specific CD4+ and CD8+ memory T cells have been observed in both healthy individuals and cancer patients. However, while the function of anti-regulatory Arg1-specific CD4+ T cells has been characterized, our knowledge of CD8+ Arg1-specific T cells is only scarce. In the current study, we describe the immune-modulatory capabilities of CD8+ Arg1-specific T cells. We generated CD8+ Arg1-specific T cell clones to target Arg1-expressing myeloid cells. Our results demonstrate that these T cells recognize both malignant and nonmalignant regulatory myeloid cells in an Arg1-expression-dependent manner. Notably, Arg1-specific CD8+ T cells possess cytolytic effector capabilities. Immune modulatory vaccines (IMVs) represent a novel treatment modality for cancer. The activation of Arg1-specific CD8+ T cells through Arg1-based IMVs can contribute to the modulatory effects of this treatment strategy.